TOKSISITAS FRAKSI n-HEKSAN DAN ETIL ASETAT DARI EKSTRAK LIMBAH KULIT KAYU BAKAU (Rhizophora apiculata Blume) TERHADAP RAYAP TANAH (Coptotermes curvignathus Holmgren) - . Alkhadi; . Muflihati (Universitas Tanjungpura, 2017)
Bakau (Rhizophora apiculate Blume) has the potential as natural preservatives, especially on the bark. The active chemical components contained in extracts of Bakau bark are tannins, saponins, and flavonoids. The objectives of the study were to determine the toxicity of extract of n-hexane fraction and ethyl acetate fraction of R. apiculata bark on subterranean termites Coptotermes curvignathus Holmgren and to evaluate the optimal concentration of extract of n-hexane fraction and ethyl acetate fraction of R. apiculata bark against subterranean termites Coptotermes curvignathus Holmgren. The method used in this research is a Completely Randomized Design with Factorial consisting of two factors. First factor consist of n-hexane fraction and ethyl acetate fraction, and second factor consist of six concentrations i.e. 0%; 2%; 4%; 6%; 8%; and 10%. All treatment was conducted on four replications. Medium for testing with subterranean termites was a glass jar containing 10 gram sand and 45 termites worker and 5 termites soldier. Cellulose paper contained extract of n-hexane fraction and ethyl acetate fraction are used as a food source for termites for 21 days. After that the mortality of termites and weight loss of cellulose paper was measure. Result of research showed that concentration 8% and 10% both on extract of n-hexane fraction and ethyl acetate fraction has a high antitermite’s activity with mortality value ≥ 95%. The optimal concentration was achieved on concentration 8% both on extract of n-hexane fraction and ethyl acetate fraction.Keywords : Antitermites, Bark, Coptotermes curvignathus, Rhizophora apiculata, Toxicity